Telecentre, Tourism and Their Impacts on Bario, Malaysia - Lo, May Chiun; Cheuk, Sharon; Azuriaty, Atang (IDOSI Publication, 2014)
It is undeniable that ICTs play an important role in alleviating poverty as it has the capacity to generate more income for the local communities and subsequently increase their standard of living. Past researchers have evidenced that ICTs, in the form of telecasters, have contributed to tourism development in rural destinations. In our study, we examine the impact of the telecaster on tourism, as well as tourism’s impact on the community in a rural destination from the economic, socio-cultural and environmental perspective. We also examine the community’s attitude towards tourism seasonality and future tourism development policies. 231 respondents comprising of residents of a rural tourism destination in Sarawak, Malaysia took part voluntarily in this study. To assess the developed model, SmartPLS 2.0 (M3) was applied based on path modelling and then bootstrapping with 200 re-samples was applied to generate the standard error of the estimate and t-values. The findings suggested that the telecaster has had a positive impact on the tourism development in Bario, which subsequently yielded positive economic, social and environmental impacts to the said destination. It was also noted that residents preferred that tourism season ability be reduced and more tourism development be implemented, in Bario. Implications of these findings were further discussed.